THE ROLE OF PSYCHOLOGICAL METHODS IN INCREASING THE EDUCATIONAL EFFICIENCY OF TEACHING PSYCHOLOGY (Universal International Scientific Journal, 2026)
This article discusses the main psychological methods used in teaching psychology, their content and role in the educational process. In particular, the advantages of the methods of explanation, conversation, observation, role-playing, training, interactive and problem-based learning are analyzed. The importance of these methods in the psychological development of students, the formation of independent thinking and communication skills is also revealed.
Keywords: psychology education; teaching methods; observation method